2011
DOI: 10.1021/ic200279g
|View full text |Cite
|
Sign up to set email alerts
|

Pyridazine- versus Pyridine-Based Tridentate Ligands in First-Row Transition Metal Complexes

Abstract: A series of first-row transition metal complexes with the unsymmetrically disubstituted pyridazine ligand picolinaldehyde (6-chloro-3-pyridazinyl)hydrazone (PIPYH), featuring an easily abstractable proton in the backbone, was prepared. Ligand design was inspired by literature-known picolinaldehyde 2-pyridylhydrazone (PAPYH). Reaction of PIPYH with divalent nickel, copper, and zinc nitrates in ethanol led to complexes of the type [Cu(II)(PIPYH)(NO(3))(2)] (1) or [M(PIPYH)(2)](NO(3))(2) [M = Ni(II) (2) or Zn(II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Intra ligand bond lengths have typical values for sp2 hybridized atoms and are in accordance with the literature data[24][25][26]. The N3-C6 and N6-C15 bonds have lengths that correspond to localized double bonds.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Intra ligand bond lengths have typical values for sp2 hybridized atoms and are in accordance with the literature data[24][25][26]. The N3-C6 and N6-C15 bonds have lengths that correspond to localized double bonds.…”
supporting
confidence: 88%
“…As the single crystal X-ray diffraction measurement confirmed that Hz•HCl exists in the diazine ring in -NH tautomeric form [20] it was expected to keep it in its Schiff base HzDPK, too. furthermore, the selected structural parameters are given in The CSD contains the structural data for three previously reported octahedral Zn(II) complexes with structurally related 1-hydrazinophthalazine and 3-chloro-6-hydrazinopyridazine based Schiff bases, refcodes: DITQOO [24] FARCEI [25] and CAJJAB [26]. In DITQOO and FARCEI structures, coordination mode of the tridentate ligands is analogous to that of HpDPK, while in CAJJAB both nitrogen atoms of the pyridazine ring are involved in coordination, thus forming a bridge between two metal atoms.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure (b), the cyclic voltammogram of 2 displays two reversible reduction waves, which are assigned to the consecutive of Co(III)/Co(II) and Co(II)/Co(I) redox process . The first pair of oxidation–reduction peaks corresponding to the oxidation–reduction couples Co(III)/Co(II), Epa 1 = −0.814 V, Epc 1 = −1.212 V, the average formal potential [E 1/2 = (Epa 1 + Epc 1 )/2] is −1.013 V, the peak‐to‐peak separation between the anodic and cathodic (ΔEp 1 ) is 0.916 V and the proportional of the peak current (ipc 1 = −2.96 μA) /(ipa 1 = 1.76 μA) is 1.42.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in figure 8, the Co(II) complexes display two reversible redox waves, which are assigned to consecutive Co(II)/Co(I) and Co(III)/Co(II) redox processes [46]. The first pair of oxidationreduction peaks correspond to oxidation-reduction couples Co(III)/Co(II); Epa 1 = 0.107 V, Epc 1 = −0.829 V, with average formal potential [E 1/2 = (Epa 1 +Epc 1 )/2] is −0.358 V. The peak-to-peak separation between the anodic and cathodic processes (ΔEp 1 ) is 0.936 V and the proportion of the peak current (ipa 1 /ipc 1 ) is 0.621.…”
Section: Electrochemistry Studiesmentioning
confidence: 99%